2018
DOI: 10.1016/j.nicl.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in white matter alterations following repetitive subconcussive head impacts in collegiate ice hockey players

Abstract: ObjectiveRepetitive subconcussive head impacts (RSHI) may lead to structural, functional, and metabolic alterations of the brain. While differences between males and females have already been suggested following a concussion, whether there are sex differences following exposure to RSHI remains unknown. The aim of this study was to identify and to characterize sex differences following exposure to RSHI.MethodsTwenty-five collegiate ice hockey players (14 males and 11 females, 20.6 ± 2.0 years), all part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 58 publications
4
43
1
2
Order By: Relevance
“…Relation to previous investigations. A variety of previous investigations into the effects of sports participation, repetitive head impacts and white matter tissue properties of athletes have used the diffusion tensor (DTI) model (Bahrami et al, 2016;Basser et al, 1994;Bazarian et al, 2014;Burzynska et al, 2016;Chang et al, 2015;Chun et al, 2015;Churchill et al, 2017aChurchill et al, , 2017bDavenport et al, 2016aDavenport et al, , 2016bDavenport et al, , 2014Deng et al, 2018;Duru and Balcioglu, 2018;Gajawelli et al, 2013;Hänggi et al, 2015Hänggi et al, , 2010Jäncke et al, 2009;Koerte et al, 2012;Kuzminski et al, 2018;Lao et al, 2015;Marchi et al, 2013;Mayinger et al, 2018;McAllister et al, 2014;Merchant-Borna et al, 2016;Myer et al, 2018Myer et al, , 2016aMyer et al, , 2016bPark et al, 2015;Saghafi et al, 2018;Schlaffke et al, 2014;Schranz et al, 2018;Sollmann et al, 2018;Stamm et al, 2015;Yuan et al, 2018) . The studies investigating the effects of elite sports participation commonly report lower fractional anisotropy (FA) and higher mean diffusivity (MD) between athletes and non-athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relation to previous investigations. A variety of previous investigations into the effects of sports participation, repetitive head impacts and white matter tissue properties of athletes have used the diffusion tensor (DTI) model (Bahrami et al, 2016;Basser et al, 1994;Bazarian et al, 2014;Burzynska et al, 2016;Chang et al, 2015;Chun et al, 2015;Churchill et al, 2017aChurchill et al, , 2017bDavenport et al, 2016aDavenport et al, , 2016bDavenport et al, , 2014Deng et al, 2018;Duru and Balcioglu, 2018;Gajawelli et al, 2013;Hänggi et al, 2015Hänggi et al, , 2010Jäncke et al, 2009;Koerte et al, 2012;Kuzminski et al, 2018;Lao et al, 2015;Marchi et al, 2013;Mayinger et al, 2018;McAllister et al, 2014;Merchant-Borna et al, 2016;Myer et al, 2018Myer et al, , 2016aMyer et al, , 2016bPark et al, 2015;Saghafi et al, 2018;Schlaffke et al, 2014;Schranz et al, 2018;Sollmann et al, 2018;Stamm et al, 2015;Yuan et al, 2018) . The studies investigating the effects of elite sports participation commonly report lower fractional anisotropy (FA) and higher mean diffusivity (MD) between athletes and non-athletes.…”
Section: Discussionmentioning
confidence: 99%
“…amygdala, hippocampus, basal ganglia) white matter. A paucity of articles have studied differences in either major (Bahrami et al, 2016;Bazarian et al, 2014;Churchill et al, 2017aChurchill et al, , 2017bDavenport et al, 2016aDavenport et al, , 2016bKoerte et al, 2012;Kuzminski et al, 2018;Mayinger et al, 2018;McAllister et al, 2014;Merchant-Borna et al, 2016;Saghafi et al, 2018;Sollmann et al, 2018;Stamm et al, 2015;Yuan et al, 2018) or cortical and subcortical (Mayer et al, 2017) white matter between collision sport participants and controls (i.e., non-athletes, non-collision sport athletes, within-subject longitudinal), but few have looked at all three to fully characterize the effects of sports participation.…”
Section: Introductionmentioning
confidence: 99%
“…AD represents the magnitude of diffusion along the direction of axons, and an AD reduction is often interpreted as a reflection of compromised axonal membrane integrity or axonal injury. 25,26 Although there are some opposing data, 27,28 studies have shown that contact-sport athletes had significantly lower MD in the corpus callosum than noncontact-sport athletes at preseason baseline. 29 Previous studies further reported that significant preseason to postseason decreases in MD and AD were observed in widespread white matter areas in high school football players, [30][31][32] and that the similar reduction in AD was found in youth football players at postseason.…”
Section: Discussionmentioning
confidence: 99%
“…Three serum samples in the football group were not assessed for biomarkers due to hemolysis, and a boxplot analysis identified 1 data point for Tau and NfL in the crosscountry group to be an unexplainable outlier, which was excluded from the analysis. As a result, 28 imaging data (n=20 football, n=8 cross-country) and 30 blood biomarker data (n=22 football, n=7 cross-country) were valid for the group difference analysis. We used 24 completed sets of the imaging-blood biomarker data (n=17 football, n=7 cross-country) for the association analysis.…”
Section: Demographicsmentioning
confidence: 95%
“…Though neuroimaging (e.g., functional MRI, DTI) can identify functional impairments and changes in white matter microstructure, we do not understand the clinical implications of these measures. [11][12][13][14][15] Moreover, on-field RHI exposure varies greatly in terms of magnitude, timing, type, and location of impact. [3][4][5][6] Variability in RHI exposure likely contributes to conflicting results across studies.…”
Section: Introductionmentioning
confidence: 99%